Trends and hotspots on hymenoptera venom immunotherapy: a bibliometric and visualized analysis of research from 2014 to 2024 - Luo, Yun; Guan, Minxia; Yu, Yichuan (Frontiers in Immunology, 2025)
ObjectiveRecently, the application of hymenoptera venom immunotherapy (VIT) has been extensively studied in the medical community. Nevertheless, there are still very few bibliometric analyses devoted to this field. Therefore, this study aims to provide a comprehensive overview of the development of research in the past 11 years and clarify future research directions and trends.MethodsFrom 2014 to 2024, articles related to “hymenoptera venom immunotherapy “and “Allergy” were from the core collection of Web of Science. This visual analysis included examining annual productivity, cooperation between countries and institutions, co-cited references, author and journal cooperation networks, keyword co - occurrence, and their respective clustering and trends.ResultsA total of 332 articles on the allergy caused by hymenoptera VIT were included in this study. Germany, Azienda Ospedaliera Universitaria Integrata Verona and Golden, David B K are the most productive countries and institutions respectively. Analysis of the top 10 literatures with co-citation frequency found that 4 were expert consensus and guidelines, 4 were single-center (or multi-center), open, randomized controlled trials, and 2 were systematic reviews. Keyword cluster analysis showed that wasps were identified as the primary focus of hymenoptera VIT in the past, and mastocytosis and hymenopteran venom allergy were the current research hotspots.ConclusionRecent studies on hymenoptera VIT have shown that today’s VIT increasingly emphasizes individualized and refined treatment. However, there is a lack of evidence of multicenter randomized controlled trials (RCTs) in this field. Further investigation is warranted to bridge this research gap.